2019
DOI: 10.1074/jbc.ra119.007697
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants for accurate dephosphorylation of RNA polymerase II by its cognate C-terminal domain (CTD) phosphatase during eukaryotic transcription

Abstract: Edited by John M. Denu The C-terminal domain (CTD) of RNA polymerase II contains a repetitive heptad sequence (YSPTSPS) whose phosphorylation states coordinate eukaryotic transcription by recruiting protein regulators. The precise placement and removal of phosphate groups on specific residues of the CTD are critical for the fidelity and effectiveness of RNA polymerase II-mediated transcription. During transcriptional elongation, phosphoryl-Ser 5 (pSer 5) is gradually dephosphorylated by CTD phosphatases, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In particular, it can interact with the CTD Ser5 kinase Kin28 to dephosphorylate CTD Ser5P and function in transcription initiation [ 8 ]. In addition, Ssu72 associates with the CTD phosphatase Fcp1 and Ctk1, which phosphorylates Ser2P in yeast, although some studies have revealed that Ssu72 has no Ser2P phosphatase activity because the Tyr1 residue does not fit into the tight β-turn of Ssu72 [ 8 , 26 , 27 , 28 ]. Ssu72 depletion can induce Fcp1 inactivation and early Ser2 phosphorylation by Ctk1, indicating that Ssu72 can tightly coordinate with various kinases and phosphatases during the transcription cycle [ 29 ].…”
Section: Mechanism By Which Ssu72 Phosphatase Regulates Gene Exprementioning
confidence: 99%
“…In particular, it can interact with the CTD Ser5 kinase Kin28 to dephosphorylate CTD Ser5P and function in transcription initiation [ 8 ]. In addition, Ssu72 associates with the CTD phosphatase Fcp1 and Ctk1, which phosphorylates Ser2P in yeast, although some studies have revealed that Ssu72 has no Ser2P phosphatase activity because the Tyr1 residue does not fit into the tight β-turn of Ssu72 [ 8 , 26 , 27 , 28 ]. Ssu72 depletion can induce Fcp1 inactivation and early Ser2 phosphorylation by Ctk1, indicating that Ssu72 can tightly coordinate with various kinases and phosphatases during the transcription cycle [ 29 ].…”
Section: Mechanism By Which Ssu72 Phosphatase Regulates Gene Exprementioning
confidence: 99%
“…For example, MS analysis revealed the capability of FCP1 (the phosphatase responsible for recycling RNAP II) to dephosphorylate most of the CTD residues. 52 MS was likewise used to show that Ssu72 (a phosphatase responsible for dephosphorylating the Ser5 conserved across yeast and human) exhibits surprisingly high specificity towards Ser5 but not Ser2 even though both serines are part of an SP motif ( Fig. 3a ).…”
Section: Characterizing the Specificity Of Ctd Kinases And Phosphatasesmentioning
confidence: 99%
“…3a ). 52 These conclusions prompted investigators to take a closer look into the crystal structures of Ssu72, ultimately revealing that the narrow and deep active site imposes steric restrictions which regulate its specificity limited to Ser5 but not Ser2. 52 …”
Section: Characterizing the Specificity Of Ctd Kinases And Phosphatasesmentioning
confidence: 99%
“…Molecular modeling studies predict that the presence of cis-proline significantly disrupts the active site of SCP1, thus making SCP1 preferentially act on serine residues proximal to transprolines [154]. Ssu72 is ubiquitously expressed and acts only on CTD repeats when prolines are in cis conformation [153,155,157].…”
Section: Crosstalk Between Individual Ctd Modificationsmentioning
confidence: 99%